Adherence and treatment patterns of disease-specific drugs among patients with pulmonary arterial hypertension: A nationwide, new-user cohort study - Tsai, Cheng-Yu; Shen, Chuan-Wei; Lai, Hsuan-Lin; Chen, Chung-Yu (Frontiers in Pharmacology, 2023)
Background: Pulmonary arterial hypertension (PAH) is an incurable pulmonary disease that might result in right heart failure and death. Treatment guidelines recommend upfront or sequential combination therapy for patients with PAH. Recently, several PAH-targeted medications have been approved in Taiwan. This study aimed to investigate treatment patterns and medication adherence in real-world settings. Method: This was a new-user design study on patients treated with PAH-specific medication between 1 January 2014, and 31 December 2019. Data were extracted from the National Health Insurance Research Database. Medication adherence was evaluated by the proportion of days covered (PDC). Adherence was defined as PDC ≥ .8. Statistical analyses were performed to compare the study outcomes. Logistic regression analysis was performed to identify the association between baseline characteristics and adherence. P < .05 indicated statistical significance. Results: A total of 1,900 patients with PAH were identified, and 75.3% of them were females. The mean (standard deviation (SD)) age was 57.2 (17.5) years. Only 23 (1.2%) patients began the initial combination therapy. A total of 148 (7.8%) patients switched their initial treatment to another treatment, and 159 (8.4%) patients had sequential combination therapy. The most common combination therapy was endothelin receptor antagonist (ERA) plus phosphodiesterase-5 inhibitor (PDE5i), mostly macitentan plus sildenafil, for initial or sequential combination. The mean (SD) PDC was .71 (.33), and 1,117 (58.8%) patients were adherent. A significant difference in mean PDC was observed between initial ERA users and PDE5i users (p < .0001). No factor was significantly associated with medication adherence. Conclusion: Patients with PAH mostly initiated sildenafil as monotherapy, and macitentan was added as a sequential combination therapy. The initial ERA and combination groups showed higher medication adherence. Further investigations are needed to identify other factors associated with adherence.